Comparative presentation of environmental protection in the criminal laws of Kosovo and Albania - Musa, Mexhit (Technium Social Sciences Journal, 2022)
Today, environmental protection is almost one of the most problematic issues facing modern society. This is because the ambiguous impact on the environment is directly related to life and health. This justifies the treatment of this issue in this dissertation! When it comes to protecting the environment or the environment in general, modern society foresees some measures in the function of this protection. Given that the problem of environmental protection is not only a national concern, it is a problem at the global level. As a result of the work of various international organizations, within the framework of their national legislation, provisions and laws have been created that sanction environmental protection violations. The Republic of Kosovo regulated the issue of environmental protection with a special law. However, in order to further implement this protection, in the Criminal Code of the Republic of Kosovo, which entered into force on January 1, 2013, a special chapter provides for some legal acts that cause damage to environmental protection. This chapter in the Criminal Code is called "Criminal offense against environmental protection", referring to the group protection of the facility. This work deals with "Protection of the environment in terms of its legal protection" (Sakib Softić, Međunarodno pravo, Sarajevo 2012.godine). Also, for the purposes of this work, contemporary acts were used, which regulate the issue of environmental protection, as well as various statistical data that are of interest for solving this problem. (Mučibabić S, 1960. Sarajevo). Therefore, we consider worthy of thinking about solving this problem, and on the territory of Kosovo, considering the fact that this topic is very little represented at academic levels.